Establishment of Public Health Management Cadre in India and Guidelines for Implementation, 2022 - Piyush Kumar (Public Health Open Access, 2022)
National Health Policy (NHP) 2017 proposed that a multi/interdisciplinary health workforce is necessary for managing programs under National Health Mission. National Health Policy 2017 considered creating Public Health Management Cadre (PHMC) in all States.
Keywords: Public Health Management; Public Health Cadre; Health Policy; India